Transcription annotée du manuscrit : Ms 18305 de la Biblioteca Nacional de España - Monique Combescure Thiry (Les Cahiers de Framespa)
The manuscript Ms 18305 of the Biblioteca Nacional de España is one of the rare exemplaries that reached to us. It describes the genealogies of some important Aragonese families all starting by, at least, a Jewish ancestor. After an index of the different family names, the document finishes by the list of the sambenitos of the city of Hijar.